Features of urban food and nutrition security and considerations for successful urban programming - Ruel, Marie T.; Garrett, James L. (Food and Agriculture Organization of the United Nations, 2004)
In this paper we discuss the wide disparities that exist in childhood malnutrition, food insecurity and livelihoods within urban areas which, when combined with the mobility of urban residents, add to the complexity of designing, targeting and implementing urban programmes. Livelihood security in urban areas is dependent on cash income, especially for food expenditures, and hence employment. For women, employment brings about the need for support with childcare; we analyse a programme that provides the double benefit of delivering affordable and reliable childcare for extended hours, and allowing women to secure a more formal employment and obtaining employment benefits. Other factors that need to be considered in shaping urban programmes include land and housing security, the crime and violence situation, the availability and nature of social networks, and governance issues. Finally, we discuss potential strategic responses to the challenges of urban programming.